2019
DOI: 10.1177/1533033819883633
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA GM16343 Promotes IL-36β to Regulate Tumor Microenvironment by CD8+T cells

Abstract: Objective: To investigate the effect of long noncoding RNA GM16343 on interleukin 36β promotion of CD8+T cells in tumor microenvironment regulation. Methods: The differentially expressed long noncoding RNA in interleukin 36β-stimulated mouse CD8+T cells was screened by gene chip technology, and the significant differentially expressed long noncoding RNAs were verified by real-time polymerase chain reaction. The lentiviral vector that overexpresses or knockdown GM16343 was constructed, transfected into CD8+T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…For instance, the downregulated lncRNA AGER has been demonstrated to be closely related to T cell status in lung cancer [ 10 ]. lncRNA GM16343 is regulated by interleukin 36 β to strengthen the antitumor immune response of CD8 + T cells [ 11 ]. lncRNA LINK-A has been demonstrated to downregulate antigen presentation and intrinsic suppression in triple-negative breast cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the downregulated lncRNA AGER has been demonstrated to be closely related to T cell status in lung cancer [ 10 ]. lncRNA GM16343 is regulated by interleukin 36 β to strengthen the antitumor immune response of CD8 + T cells [ 11 ]. lncRNA LINK-A has been demonstrated to downregulate antigen presentation and intrinsic suppression in triple-negative breast cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lnc-Tim3 can exacerbate CD8+ T cell exhaustion through binding to Tim-3 and triggering nuclear translocation of Bat3 in liver cancer [ 26 ]. LncRNA GM16343 can induce IL-36 β to modulate tumor microenvironment via CD8+ T cells [ 27 ]. LINC00301 can facilitate lung cancer progression and triggers an immune-suppressing microenvironment through regulating the HIF1 α [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research on mice found that difference of lncRNA-GM16343 was the most obvious between the groups by taking advantage of gene chip technology in mouse CD8 + T cells stimulated by IL-36β [ 102 ]. GM16343 stimulated the secretion of IFN-γ in CD8 + T cells, markedly reduced tumor volume of mice, and potently prolonged the survival time.…”
Section: Introductionmentioning
confidence: 99%
“…GM16343 stimulated the secretion of IFN-γ in CD8 + T cells, markedly reduced tumor volume of mice, and potently prolonged the survival time. It was indicated GM16343 profoundly dampened tumor growth through affecting antitumor immune function of CD8 + T cells (Table 1 ) [ 102 ]. Intriguingly, a recent study conducted by Wang et al demonstrated that exosomes originated from exhausted CD8 + T cells could be internalized by non-exhausted CD8 + T cells, and impeding proliferation capacity and the secretion of cytokines, i.e.…”
Section: Introductionmentioning
confidence: 99%